Mutations in HIV-1 gag and pol compensate for the loss of viral fitness caused by a highly mutated protease - Kozísek, Milan; Henke, Sandra; Sasková, Klára Grantz; Jacobs, Graeme Brendon; Schuch, Anita; Buchholz, Bernd; Müller, Viktor; Kräusslich, Hans-Georg; Rezácová, Pavlína; Konvalinka, Jan; Bodem, Jochen (Antimicrobial agents and chemotherapy, 2012)
During the last few decades, the treatment of HIV-infected patients by highly active antiretroviral therapy, including protease inhibitors (PIs), has become standard. Here, we present results of analysis of a patient-derived, multiresistant HIV-1 CRF02_AG recombinant strain with a highly mutated protease (PR) coding sequence, where up to 19 coding mutations have accumulated in the PR. The results of biochemical analysis in vitro showed that the patient-derived PR is highly resistant to most of the currently used PIs and that it also exhibits very poor catalytic activity. Determination of the crystal structure revealed prominent changes in the flap elbow region and S1/S1' active site subsites. While viral loads in the patient were found to be high, the insertion of the patient-derived PR into a HIV-1 subtype B backbone resulted in reduction of infectivity by 3 orders of magnitude. Fitness compensation was not achieved by elevated polymerase (Pol) expression, but the introduction of patient-derived gag and pol sequences in a CRF02_AG backbone rescued viral infectivity to near wild-type (wt) levels. The mutations that accumulated in the vicinity of the processing sites spanning the p2/NC, NC/p1, and p6pol/PR proteins lead to much more efficient hydrolysis of corresponding peptides by patient-derived PR in comparison to the wt enzyme. This indicates a very efficient coevolution of enzyme and substrate maintaining high viral loads in vivo under constant drug pressure.
Keywords: virová nálož; inhibitory HIV-proteasy; Cell Line; krystalografie rentgenová; HIV-1; mutace; vysoce aktivní antiretrovirová terapie; Genes, gag; HEK293 buňky; genové produkty pol - virus lidské imunodeficience; HIV Infections; pol Gene Products, Human Immunodeficiency Virus; geny gag; molekulární sekvence - údaje; HEK293 Cells; HIV Protease Inhibitors; HIV infekce; Crystallography, X-Ray; Viral Load; peptidové fragmenty; Drug Resistance, Viral; lidé; HIV Protease; Humans; Genes, pol; HIV-proteasa; buněčné linie; virová léková rezistence; Molecular Sequence Data; Antiretroviral Therapy, Highly Active; Mutation; genové produkty gag - virus lidské imunodeficience; Peptide Fragments; gag Gene Products, Human Immunodeficiency Virus; geny pol